THE ROLE OF TRUST IN MEDIATING CUSTOMER SATISFACTION AND CUSTOMER ENGAGEMENT TOWARDS LOYALTY OF BPRS AL HIJRAH THAYIBAH DEPOSITORS - Kurniadi, Dertian Ruly; Rasyid, Harun Al; Sudaryanti, Dwiyani (Pena Cendekia Insani, 2026)
This study aims to analyze the influence of customer satisfaction and customer Engagement on depositor loyalty through trust. The sample size in this study was 100 respondents. The analysis technique used SEM PLS. The analysis shows that customer satisfaction influences trust. Customer Engagement influences trust. Customer satisfaction influences depositor loyalty. Customer Engagement influences depositor loyalty. Trust influences depositor loyalty. Trust mediates the relationship between customer satisfaction and depositor loyalty. Trust mediates the relationship between customer Engagement and depositor loyalty.